1971
DOI: 10.1111/j.1365-2141.1971.tb03424.x
|View full text |Cite
|
Sign up to set email alerts
|

Annotation: THE ANAEMIA OF CHRONIC DISORDERS

Abstract: Although the anaemia associated with chronic disorders is one of the most frequently encountered forms of anaemia, particularly in hospital patients, it has not received the distinction which it deserves, in part, perhaps, because of the lack of an appropriate name. The term ‘simple chronic anaemia’ is most inappropriate because the pathogenesis of the anaemia involves the delicate control mechanisms of erythropoiesis and these are not simple. The title ‘anaemia of chronic infections’ is much too restrictive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
127
1
9

Year Published

1972
1972
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(138 citation statements)
references
References 10 publications
1
127
1
9
Order By: Relevance
“…Impaired release of the metal from the reticuloendothelial system to circulation (Cartwright & Lee, 1971;Konijn & Hershko, 1977) and acceleration of flux of plasma iron into hepatic storage sites (Biesel, 1976) have been demonstrated in inflammatory conditions. Biesel et al (1974) demonstrated increase in ferritin synthesis and Heilmeyer & Wohler (1961) reported accumulation of iron in storage tissues during acute=chronic inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired release of the metal from the reticuloendothelial system to circulation (Cartwright & Lee, 1971;Konijn & Hershko, 1977) and acceleration of flux of plasma iron into hepatic storage sites (Biesel, 1976) have been demonstrated in inflammatory conditions. Biesel et al (1974) demonstrated increase in ferritin synthesis and Heilmeyer & Wohler (1961) reported accumulation of iron in storage tissues during acute=chronic inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Beta thalassaemia minor is the most common form of thalassemia. 4 Most homozygotes suffer from a severe syndrome and require regular blood transfusions to survive.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] These indices can be used as preliminary screening tools which can help distinguish between Iron deficiency anemia(IDA) and Beta thalassemia trait (BTT). 3 In a tertiary level health care center, it is important to identify suspect BTT individuals from the routine cbc workload.…”
Section: Introductionmentioning
confidence: 99%
“…When 59Fe haemoglobin is injected intravenously it is rapidly cleared by the reticuloendothelial (RE) system and studies of radioactive iron utilization following its administration have shown diminished red cell incorporation in patients with generalized Hodgkin's disease (Haurani, Young and Tocantins, 1963). This is thought to be due to a failure of RE cells to release iron derived from the catabolism of haemoglobin, and this state is associated with a low plasma iron concentration and consequent impaired delivery to the bone marrow (Cartwright and Lee, 1971). An alternative method of measuring RE cell iron release involves a double isotope technique in which 55Fe labelled iron dextran replaces labelled haemoglobin and 59Fe labelled transferrin is used to measure plasma iron utilization (Beamish et al, 1971).…”
mentioning
confidence: 99%